Difficulties reported by Medicine students during pandemic period: a Study at a university in the northern region of Brazil (Research, Society and Development, 2022)
The purpose of this article is to analyze the difficulties reported by students of a medical course during the pandemic period. The locus of research was a higher education institution in the North of Brazil and the bachelor's degree in Medicine, involving 160 respondents. The methodological procedures used were, for the collection of information, the application of a questionnaire and for the analysis of data, the content analysis, with a survey of responses, categorization and analysis by categories, six categories were highlighted with a predominance of responses associated with the themes study/time and psychological suffering. It is concluded that students have different types of difficulties and fears during the pandemic, with a predominance of those associated with the fear resulting from the pandemic and not having the teaching and learning processes guaranteed by elements internal and external to the Higher Education Institution that are linked.